2021
DOI: 10.3390/agriculture11050465
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Successive Harvesting of Rocket and Spinach Baby Leaves Enhanced Their Quality and Production Efficiency

Abstract: Rocket and spinach baby leaves are valuable commodities since they are basic components of popular ready-made salads. Two methods may follow after harvesting: establishment of new cultivations or successive revegetations and harvests. This study aimed to investigate the yield and nutritional value of rocket and spinach baby leaves after individual cultivations or successive revegetations in a floating system to improve their production strategy. The crops were cultivated in a greenhouse for seven weeks using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…Interestingly, in that same study, the reported cumulative fresh yield of three consecutive harvests of the same plots reached 18,999 and 13,900 kg ha -1 in the two respective seasons of the experiment. Thus, quinoa yield may be significantly increased by growing the plants after the first harvest and harvesting them at intervals, similar to spinach, alfalfa, elephant grass, and other leafy field crops [43][44][45]. However, multiple harvests may eventually reduce quinoa plant yield and quality [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in that same study, the reported cumulative fresh yield of three consecutive harvests of the same plots reached 18,999 and 13,900 kg ha -1 in the two respective seasons of the experiment. Thus, quinoa yield may be significantly increased by growing the plants after the first harvest and harvesting them at intervals, similar to spinach, alfalfa, elephant grass, and other leafy field crops [43][44][45]. However, multiple harvests may eventually reduce quinoa plant yield and quality [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple harvests may eventually reduce quinoa plant yield and quality [42]. Another suggested possibility for maximizing quinoa yield while retaining quality is to establish a new cultivation on the same plot following harvest, similar to spinach and rocket [45]. However, as pests and diseases may develop with high plant density and re-seeding of the same crop on the same plot, crop rotation should be considered to reduce possible adverse effects [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roquette is characterized by a pungent and bitter taste, provided by a range of beneficial compounds (Vitamin C, carotenoids, phenolics, and glucosinolates) (Table 2) that contribute to its antioxidant capacity. Conversely, it can also accumulate anti-nutrients (e.g., nitrates) and heavy metals [27][28][29][30][31]. Besides the culinary uses, roquette has interesting medicinal properties, such as diuretic and depurative effects [26], and its extracts have antimicrobial properties [32], antigenotoxic properties in D. melanogaster [33], and cytotoxic effects in tumoral cell lines [34].…”
Section: Roquettementioning
confidence: 99%
“…In today's society, people demonstrate a growing propensity to stay informed about environmental issues, probably due to concerns about the possible adverse effects of climate change on human health. This concern has led consumers to adopt healthy eating habits [1,2], rich in vegetables with high antioxidant content, capable of preventing or reducing health problems [3,4]. However, in modern society, people often find themselves under pressure due to the hectic pace of their days.…”
Section: Introductionmentioning
confidence: 99%